PERENCANAAN STRUKTUR GEDUNG BERTINGKAT TINGGI BERDASARKAN SNI 03-1726-2010 - Febrianto, Andru Fajar; Harimurty, Krisna; Indarto, Himawan; Sukamta, Sukamta (Jurnal Karya Teknik Sipil, 2013)
Structure design of a high rise building using SNI 03-1726-2010 on this final report are designed to seismic zoning area of Semarang city using the Moment Resisting Frame System method with configuration structure collapse the Special Moment Resisting Frame System (SRPMK). The Moment Resisting Frame System method, where the system basically has the burden resisting space frame gravity and lateral loads. The Special Moment Resisting Frame System (SRPMK) election expected to be a high rise building structure behave ductile, because structure is ductile energy dissipation capacity were large and has a good carrying capacity in the resist earthquake loads. This system is planned to use the concept of strong column weak beam, where the vertical elements of the structure (column) should be stronger than the horizontal elements of the structure (beam), to be plastically formed joints first on the beam. The joints meeting of the beam-column should also be well designed to avoid collapse first. This system can be used for planning a high rise building in an earthquake zone areas that have been determined. The analysis output structure of a high rise building using SNI 03-1726-2010 applied SAP2000 v10 software to determine the fundamental period of the structure and the forces acting on the structure. In the configuration of the structure collapse the Special Moment Resisting Frame System (SRPMK) fundamental structural period must be limited so that the structure is not very flexible. Results in the forces acting on the structure is used to design the structure of  high story building.